Analisis SWOT Usaha Keripik Mbothe (Talas) Lestari Di Desa Srabah, Kecamatan Bendungan Kabupaten Trenggalek - Pramesti, Nila Ikhrani Karunia; Setiawan, Dicky Wahyu Robi Hadi; Pamungkas, Kevin Dyo (Jurnal Ilmiah Pertanian Nasional, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in local economic growth by leveraging regional potential, such as the Lestari Mbothe (Taro) Chips MSME in Srabah Village, Trenggalek Regency, which uses local taro as its primary raw material. This study analyzed the business's internal and external conditions and formulated a development strategy using a SWOT analysis. A mixed-methods approach was applied, with a qualitative component through interviews and observations, and a quantitative component using the IFE and EFE Matrices. The analysis results indicate that strengths and opportunities outweigh weaknesses and threats, placing this MSME in Quadrant I (Strengths–Opportunities). The main strengths are the abundant availability of raw taro, its distinctive taste, and the appeal of traditional products. Opportunities are supported by the trend of consuming local food and healthy snacks. Weaknesses include limited production capacity, simple equipment, and suboptimal marketing, while threats come from competition and fluctuations in consumer purchasing power. An aggressive development strategy (SO) focuses on maximizing strengths to seize opportunities by improving product quality, packaging, marketing innovation, and expanding distribution. This is expected to increase competitiveness, support sustainable growth, and empower the rural economy. Usaha Mikro, Kecil, dan Menengah (UMKM) berperan penting dalam pertumbuhan ekonomi lokal dengan memanfaatkan potensi wilayah, seperti UMKM Keripik Mbothe (Talas) Lestari di Desa Srabah, Kabupaten Trenggalek, yang menggunakan talas lokal sebagai bahan baku utama. Penelitian ini menganalisis kondisi internal dan eksternal usaha serta merumuskan strategi pengembangan menggunakan analisis SWOT. Metode campuran (mixed methods) diterapkan, dengan pendekatan kualitatif melalui wawancara dan observasi, serta kuantitatif menggunakan Matriks IFE dan EFE. Hasil analisis menunjukkan kekuatan dan peluang lebih dominan daripada kelemahan dan ancaman, menempatkan UMKM ini di Kuadran I (Strength–Opportunities). Kekuatan utama adalah ketersediaan bahan baku talas melimpah, cita rasa khas, dan daya tarik produk tradisional. Peluang didukung tren konsumsi pangan lokal dan camilan sehat. Kelemahan meliputi kapasitas produksi terbatas, peralatan sederhana, dan pemasaran suboptimal, sementara ancaman dari persaingan dan fluktuasi daya beli konsumen. Strategi pengembangan agresif (SO) difokuskan pada memaksimalkan kekuatan untuk menangkap peluang, melalui peningkatan kualitas produk, perbaikan kemasan, inovasi pemasaran, dan perluasan distribusi. Ini diharapkan meningkatkan daya saing, mendukung pertumbuhan berkelanjutan, dan memberdayakan ekonomi pedesaan